Applications of advanced hybrid organic-inorganic nanomaterials: from laboratory to market - Sanchez, Clément; Belleville, Philippe; Popall, Michael; Nicole, Lionel (Chemical Society reviews, 2011)
Today cross-cutting approaches, where molecular engineering and clever processing are synergistically coupled, allow the chemist to tailor complex hybrid systems of various shapes with perfect mastery at different size scales, composition, functionality, and morphology. Hybrid materials with organic-inorganic or bio-inorganic character represent not only a new field of basic research but also, via their remarkable new properties and multifunctional nature, hybrids offer prospects for many new applications in extremely diverse fields. The description and discussion of the major applications of hybrid inorganic-organic (or biologic) materials are the major topic of this critical review. Indeed, today the very large set of accessible hybrid materials span a wide spectrum of properties which yield the emergence of innovative industrial applications in various domains such as optics, micro-electronics, transportation, health, energy, housing, and the environment among others (526 references).